Cyber Security Laws In India - Constitutional Implications & Gaps. - Lakshmana Kumar, M.; Saleem Akram, P. (Journal of Neonatal Surgery, 2025)
This study critically examines cybersecurity laws in India, focusing on constitutional implications & and identified gaps within the existing legal system. The study delves into legislative developments, the role of government agencies, and the issues faced in implementing and enforcing these laws. In addition, it explores the delicate balance between ensuring national security and safeguarding digital rights. This article concludes with recommendations for legal reforms to enhance cybersecurity laws' efficacy. This analysis contributes to a nuanced understanding of India's evolving landscape of cybersecurity regulations. The landscape of cybersecurity laws in India presents a complex interplay of constitutional implications and notable gaps. This article delves into the constitutional structure guiding cybersecurity regulations, examining the balance between individual privacy rights and the State's responsibility to ensure national security. Key legislation, such as the Information Tech Act of 2000 and subsequent amendments, are analyzed considering constitutional principles. Despite strides, gaps persist in addressing emerging threats, cross-border challenges, and harmonizing legal provisions. This article outlines the nuanced legal terrain, emphasizing the need for a comprehensive, adaptive legislative approach to fortify India's cybersecurity structure in the face of evolving digital landscapes.